Students’ Speaking Problems In English Presentation - Siti Sahara; Zulaikah Zulaikah; Jelita Jelita (Channing : Journal of English Language Education and Literature, 2021)
This research focused on students' speaking problems in English and the purpose of this research is to know problems happening in speaking especially when they are presented by the second semester of STKIP Nurul Huda Sukarja's English Education Program in their speaking presentations. This research used the descriptive method. The author uses observation, questionnaires, and interviews as a data collection tool. From the results of the questionnaire, psychological problems are most often problems experienced by the second semester English Education Program of STKIP Nurul Huda Sukarja with a mean of 72,73% who had a problem in vocabulary, 54,55% who have problems in grammar, 60,61% who had problems in pronunciation, 72,73% who fear of making mistake, and 57,58% who have problems in lack of confidence. In conclusion, linguistics and psychological problems are a problem that experienced by the second semester of the English Education Program of STKIP Nurul Huda Sukarja